¿Tan mortal como un conflicto armado? La violencia por pandillas y el desplazamiento forzoso en el Triángulo Norte de Centroamérica - Cantor, David James (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
The flurry of interest around the European refugee crisis, whilst plainly justified, should not have the effect of distracting international attention from equally pressing humanitarian and refugee crises in other parts of the world. As such, this article highlights the extreme nature and scale of gang violence in the Northern Triangle countries of Central America, which has resulted in substantial forced displacement of affected populations. The article argues that, despite certain commonalities with situations of internal armed conflict (such as Syria), the scenario in the Northern Triangle poses a distinct set of additional challenges for ensuring the protection of refugees and displaced persons from these countries. The urgent need to address these challenges in the Americas is no less than for those presented by the current refugee crisis in Europe.

La fascinación que rodea la presente crisis de refugiados en Europa, aunque justificada, no debe desviar la atención internacional de las crisis humanitarias y de refugiados igualmente graves que existen en otras regiones del mundo. Como tal, este artículo destaca la extrema naturaleza y escala de la violencia por pandillas en los países del Triángulo Norte de Centroamérica, la cual resulta en el desplazamiento forzoso de las poblaciones afectadas. El articulo proponeque, a pesar de ciertas paralelas con las situaciones de conflicto armado interno (como Siria), el escenario en el Triángulo Norte plantee uno conjunto distinto de retos adicionales en la búsqueda de protección para los refugiados y desplazados de estos países. La urgencia de responder a estos retos en las Américas no es menos que para los desafíos presentados por la actual crisis de refugiados en Europa.
‘As deadly as armed conflict? Gang violence and forced displacement in the Northern Triangle of Central America’
Keywords: Europa; Centroamérica; Triángulo Norte; Violencia; Pandillas; Refugiados; Desplazamiento; https://purl.org/pe-repo/ocde/ford#5.09.01